TEACHING THEME–RHEME STRUCTURES TO UZBEK LEARNERS OF ENGLISH: CHALLENGES AND SOLUTIONS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
this paper investigates the challenges faced by Uzbek learners in acquiring the concept of theme–rheme structure in English and proposes practical pedagogical solutions. Based on systemic functional linguistics and contrastive language analysis, the study identifies cross-linguistic interference and limited instructional materials as key barriers. The article argues for explicit instruction and the incorporation of functional-pragmatic tasks in the Uzbek EFL classroom to develop learners' ability to convey intended information structure accurately and fluently.